Paul, the Law, Grace and … "Cheap Grace"? - Lebedev, Vladimir (Bogoslovskie razmyšlenija, 2006)
In his ministry Paul had to deal with the critique of authoritative religious figures of that time who sought to accuse the apostle of abusing God’s grace. This paper reviews the historical approaches to Paul and his convictions about the law, grace, and the state of Gentiles and Jews before God, and then examines Paul’s teaching concerning the presumed charges. Texts from Romans are studied that reflect the character of the charges, and then those containing expositions of the concepts that clarify the situation and overturn the accusations. These concepts are law, grace, and righteousness and newness of life.